Adherence to low-carbohydrate diet in relation to gastric cancer: findings from a case-control study in Iran. Issue 4 (23rd September 2020) - Toorang, Fatemeh; Zendehdel, Kazem; Sasanfar, Bahareh; Hadji, Maryam; Esmaillzade, Ahmad
Abstract : This study examined the association between adherence to low carbohydrate diet (LCD) and risk of gastric cancer (GC). This hospital-based case-control study was conducted in Iran Cancer Institute, Tehran, Iran between 2010 and 2012. Totally, 178 patients with GC and 276 apparently healthy controls participated in this study. Cases were histo-pathologically confirmed GC patients aged ≥40 years diagnosed with GC in the last year. Dietary intakes were assessed using a validated 146-item Diet History Questionnaire. We computed the LCD score trough the protocol explained by Halton. Patients with GC were older (60.8 vs. 53.2 years, P < 0.001) and more likely to be male (74.2 vs. 63.8%, P = 0.02), married (97.8 vs. 86.6%, P < 0.001) and illiterate (62.4% vs. 26.1%, P < 0.001) than controls. Before adjusting for covariates, adherence to LCD-diet was not associated with risk of GC [odds ratio (OR) 1.31; 95% confidence interval (CI) 0.82–2.09 for highest vs. lowest tertile; P trend < 0.26]. Adjustments for several potential confounders including H-pylori infection and BMI, participants in the highest tertile of LCD score were 7% more likely to have GC than those in the lowest tertile; however, it was not statistically significant (OR 1.07; 95% CI 0.59–1.95 for highest vs. lowest tertile; P trend < 0.79). No significant association was also seen between adherence to animal- or vegetable-based LCD diet and risk of GC. In conclusion, we failed to find any evidence on the association between consumption of LCD and odds of GC. Further studies, in particular of prospective design, are required to confirm these findings.